Truncamento no português brasileiro: para uma melhor compreensão do fenômeno (Revista de Estudos da Linguagem, 2006)
This article evaluates and discusses cases of truncation in BrazilianPortuguese (BP). A general evaluation of truncated forms in BP ispresented within traditional grammatical approaches, and we alsoconsider some proposals presented in manuals of morphology.Finally, we consider some articles that focus on theoretical issuesrelated to truncation. In order to have a better understanding oftruncation in BP we organized an experiment to evaluate over ahundred truncated forms. Results from our experiment indicatethat truncated forms tend to follow general patterns, althoughsuch patterns are not categorical. We also distinguish truncatedforms from cases of reduction of lexical items. Our results offerinsights for future analyses on truncation and reduced forms inBP and may also contribute to the discussion of the interactionbetween phonology and morphology.